2014
DOI: 10.4049/jimmunol.1490012
|View full text |Cite
|
Sign up to set email alerts
|

Development and Implementation of Papillomavirus Prophylactic Vaccines

Abstract: Translation of basic scientific findings into practical patient outcomes is a significant exercise even when the goal is conceptually straightforward, as in the development of a vaccine for an infectious disease. Recognition of the association of cervical cancer with papillomavirus infection encouraged development of a vaccine to help with prevention of this very common cancer, causing over 250,000 deaths each year worldwide. To introduce a vaccine program, it was however necessary to develop a technology for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 50 publications
0
33
0
Order By: Relevance
“…Studies on HPV vaccine started in 1990s (Kahn et al, 2005;Frazer et al, 2014) and currently, HPV vaccine is not included in the national vaccine schedule. In Turkey, there are two HPV vaccines available on the market, containing 2 and 4 types of antigen, which have received authorization in 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on HPV vaccine started in 1990s (Kahn et al, 2005;Frazer et al, 2014) and currently, HPV vaccine is not included in the national vaccine schedule. In Turkey, there are two HPV vaccines available on the market, containing 2 and 4 types of antigen, which have received authorization in 2007.…”
Section: Introductionmentioning
confidence: 99%
“…In 1991, a team led by Professor Ian Frazer developed novel technology based on virus‐like particles leading to the manufacture of vaccines against the two major strains of HPV associated with cervical cancer (16 and 18) and two strains associated with genital warts (6 and 11) 15 16 achieving 83% coverage for the first dose and 70% coverage rate for the full three‐dose HPV vaccine schedule in adolescent girls turning 15 16 …”
Section: Preventing Liver Cancer and Human Papillomavirus (Hpv)‐assocmentioning
confidence: 99%
“…In 1995, Breitburd et al [25] showed that vaccination with VLPs to protect domestic rabbits against papillomas induced by cottontail rabbit papillomavirus was possible. Further studies that examine the in vitro neutralizing activity of polyclonal antisera showed that the protection was type specific and the vaccine would need to be multivalent [24]. Subsequently, it was demonstrated that after immunization, serum IgG was exudated into the genital tract, ensuring the host protection [26].…”
Section: Hpv Vaccine Developmentmentioning
confidence: 99%
“…The primary challenge for developing an HPV prophylactic vaccine was to find a source of antigens for HPV, as papillomavirus could not grow in culture. In the early 1990s, some researchers achieved expression of PV L1 and were able to produce VLPs [24]. The new challenge was proving that a vaccine based on VLPs would induce virus-neutralizing antibodies and host protection.…”
Section: Hpv Vaccine Developmentmentioning
confidence: 99%
See 1 more Smart Citation